1962
DOI: 10.1177/107769906203900403
|View full text |Cite
|
Sign up to set email alerts
|

Immunization—with and without Use of Counter-Arguments

Abstract: A n experimental study of the effects of a two-sided message suggests that it may reduce the cognitive effects of subsequent counter-propaganda but be inferior to a one-sided message in effects upon emotional responses. Both implicit and explicit twosided messages were used.the man who presents his message first has an opportunity to "immunize" his audience against subsequent arguments by an opponent. This phenomenon was demonstrated shortly after World War I1 when Lumsdaine and Janisl found that 61% of high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Yet, some scholars have found results inconsistent with the theory (e.g. Adams & Beatty, 1977;Benoit, 1991;Burgoon & Chase, 1973;Burgoon & King, 1974;Compton & Pfau, 2004;Crane, 1962;Farkas & Anderson, 1976;Lessne, 1983;Pashupati et al, 2002;Pryor & Steinfatt, 1978;Sawyer, 1973). In these experiments, inoculation treatments have been shown to be ineffective at conferring resistance.…”
Section: The Effects Of Inoculation On Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, some scholars have found results inconsistent with the theory (e.g. Adams & Beatty, 1977;Benoit, 1991;Burgoon & Chase, 1973;Burgoon & King, 1974;Compton & Pfau, 2004;Crane, 1962;Farkas & Anderson, 1976;Lessne, 1983;Pashupati et al, 2002;Pryor & Steinfatt, 1978;Sawyer, 1973). In these experiments, inoculation treatments have been shown to be ineffective at conferring resistance.…”
Section: The Effects Of Inoculation On Attitudesmentioning
confidence: 99%
“…These results help clarify the body of research on inoculation. Although a number of researchers found that inoculation can confer resistance to persuasion (e.g., McGuire, 1961aMcGuire, , 1961bMcGuire, , 1962McGuire, , 1964McGuire, , 1966Pfau et al, 1997Pfau et al, , 2001aWood, 2007), several published (e.g., Adams & Beatty, 1977;Benoit, 1991;Burgoon & Chase, 1973;Burgoon & King, 1974;Crane, 1962;Pashupati et al, 2002;Pryor & Steinfatt, 1978;Sawyer, 1973) andunpublished (e.g., Lessne, 1983) studies have documented results that failed to support the theory or failed to support specific predictions of inoculation theory. The results of this meta-analysis suggest that, across a sample of 41 published and unpublished research reports involving over 10,000 participants, inoculation treatments are more effective than no-treatment controls or supportive treatments in fostering resistance to attitude change.…”
Section: Overall Inoculation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Crane (1962) who suggested that immunization should distinguish between cognition and affect, most early inoculation studies have considered attitudes to be mainly cognitively structured, thus ignoring the potential role of affect in inoculation theory. However, more recent studies have recognized the importance of affect in inoculation (Lee & Pfau, 1997;Pfau et al, 2001) and resistance (Jacks & Devine, 2000;Zuwerink & Devine, 1996).…”
Section: Inoculation Theorymentioning
confidence: 98%
“…The purpose of inoculation theory is to keep faith, so not only can the basic process influence the effect, but also external forms affected it. Crane (1962) pointed out that the inoculation theory was influenced by the external features of attitudes [7]. He thought that we had emotional attitude and cognitive attitude which he didn't research deeply, and many researchers just studied the cognitive attitude rather emotional attitude.…”
Section: Attitudementioning
confidence: 99%